Analysis of agricultural public expenditures in Nigeria: Examination at the federal, state, and local government levels - Mogues, Tewodaj; Olofinbiyi, Tolulope; Nwoko, Chinedum; Udoh, Edet; Alabi, Reuben Adeolu; Onu, Justice; Woldeyohannes, Sileshi; Olomola, Aderibigbe (International Food Policy Research Institute, 2014)
The level of public spending on agriculture in Nigeria remains low regardless of the indicator used. Agricultural spending as a share of total federal spending averaged 4.6 percent between 2008 and 2012 and has been trending downward precipitously. In contrast, Nigeria recorded an annual average agricultural growth rate of more than 6 percent between 2003 and 2010, and agricultural gross domestic product followed an increasing trend between 2008 and 2012. Budgetary allocation to agriculture compared with other key sectors is also low despite the sector’s role in the fight against poverty, hunger, and unemployment and in the pursuit of economic development. Public investment has been stifled by the lopsided manner in which national revenue is being allocated among the three tiers of government that have responsibility for agricultural development.